(untitled) (Journal of Environmental Science and Natural Resources, 2017)
This study was conducted to know the status of physicochemical water quality parameter and heavy metal concentration in the water of Buriganga river, adjoining to Dhaka city. Water samples were collected from five different points of Buriganga river and were analyzed to determine pH, electrical conductivity (EC), total dissolved solids (TDS), dissolved oxygen (DO), biological oxygen demand (BOD), chromium (Cr), lead (Pb), cadmium (Cd), copper (Cu) and manganese (Mn) content. Most of the measured water quality parameters and concentration of heavy metals were exceeded the standard level set by ECR and ADB. Among heavy metals concentration, level of chromium and cadmium were 4-5 times higher than the standard drinking level, these results indicate that surrounding industrial wastewater discharging from textile and tannery industries, which pollute the Buriganga river water. During the observation, at Hazaribagh station BOD level was found 32 times higher than drinking water standard level and 6 times higher than standard irrigation level, indicating Buriganga river water is extremely polluted by microorganism and is not suitable for household and irrigational use. Similarly, DO level at Buriganga river water was 5 times lower than the standard level, which indicates that Buriganga river water is extremely polluted and is unsuitable for aquatic life which are dependent on DO for their sustain. In the present study, the measured level of EC, chromium, cadmium and copper were found higher level as compare to the previous studies. J. Environ. Sci. & Natural Resources, 9(2): 97-104 2016